Strange music : a Pip & Flinx adventure - Foster, Alan Dean, 1946- (Del Rey, 2017)
"Unlikely duo Pip and Flinx return to right another wrong in this all-new sci-fi adventure from one of the genre's living legends. Fans of fun, fast-paced, imaginative science fiction adventure, rejoice! #1 New York Times bestselling author Alan Dean Foster returns to his much-loved Commonwealth series with a new novel starring the indefatigable Flinx and his venomous minidrag, Pip. Facing danger and doing good is their business. provided the price is right. The unexpected return of an old friend draws Flinx and Pip to the backward planet of Largess, whose seal-like denizens' primitive technology and fractious clan politics have kept a wary Commonwealth from a profitable trade relationship. But now a rogue human employing forbidden advanced weaponry threatens to ignite a war among the Larians. And Flinx is just the man to stop it before it starts. But once on Largess, Flinx discovers his empathic abilities--usually his greatest asset--are rendered useless by the natives' unique language, which is sung rather than spoken. Worse, the abduction of a powerful chieftain's daughter has raised tensions to the boiling point. Now Flinx must depend on his own mettle--and of course Pip, the devoted minidrag with the deadly edge--to right wrongs, mend fences, and battle a cold-blooded adversary armed with enough firepower to blow them all away. and destroy the chance for peace in Largess forever. Advance praise for Strange Music "Adventure-loving readers new to the series, as well as old fans, will enjoy [Alan Dean] Foster's return to Commonwealth space."--Publishers Weekly"--